Le crochet équipoise : un moyen économique pour gérer le problème esthétique - Hiba TRIKI; Sana BEKRI; Mounir TRABELSI (International Arab Journal of Dentistry (IAJD), 2016)
Removable partial dentures often cause concern to patients; these prostheses compromise esthetics owing to their design and the visibility of hooks when placed on anterior abutments. For large posterior edentulous ridges, the practitioner must manage the problems of aesthetics and prosthetic disequilibrium due to the duality of the supporting tissues.This article presents a case of composite prosthesis in which the “equipoise” hook was used to combine between the biomechanical requirements of retention and the aesthetic demands of the patient.